2020
DOI: 10.1056/nejmoa2028436
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of SARS-CoV-2 mRNA-1273 Vaccine in Older Adults

Abstract: Background Testing of vaccine candidates to prevent infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in an older population is important, since increased incidences of illness and death from coronavirus disease 2019 (Covid-19) have been associated with an older age. Methods We conducted a phase 1, dose-escalation, open-label trial of a messenger RNA vaccine, mRNA-1273, which encodes the stabilized prefusion SARS-CoV-2 spike protein (S-2P) in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

91
1,271
6
31

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,390 publications
(1,461 citation statements)
references
References 24 publications
91
1,271
6
31
Order By: Relevance
“…Observed local reactions were almost exclusively cases of transient mild to moderate injection site pain; of the 415 total administered doses of CVnCoV at any dosage only three resulted in transient severe local pain, all after the first dose (one each in the 2, 4 and 8 µg groups). The frequency and severity of solicited systemic AEs increased with dosage level and were generally more frequent and of higher intensity after the second dose than the first, as has been observed with other mRNA SARS-CoV-2 vaccine candidates[20][21][22]. These systemic AEsmainly consisted of transient mild or moderate headache and fatigue, and to a lesser extent myalgia and chills.…”
mentioning
confidence: 57%
“…Observed local reactions were almost exclusively cases of transient mild to moderate injection site pain; of the 415 total administered doses of CVnCoV at any dosage only three resulted in transient severe local pain, all after the first dose (one each in the 2, 4 and 8 µg groups). The frequency and severity of solicited systemic AEs increased with dosage level and were generally more frequent and of higher intensity after the second dose than the first, as has been observed with other mRNA SARS-CoV-2 vaccine candidates[20][21][22]. These systemic AEsmainly consisted of transient mild or moderate headache and fatigue, and to a lesser extent myalgia and chills.…”
mentioning
confidence: 57%
“…+ T cell response was induced by mRNA-1273 vaccination. In another small study involving old adults (>56 years old), mRNA-1273 at 25 and 100 μg also demonstrated good safety and efficacy profiles (Anderson et al, 2020). Importantly, mRNA-1273 was recently tested in a large phase III COVE trial with >30,000 participants (NCT04470427) and demonstrated a 94.5% rate of protection against COVID-19 (https://investors.…”
Section: Progress Of Covid-19 Vaccine Developmentmentioning
confidence: 99%
“…An LNP-mRNA vaccine mRNA-1273 developed by Moderna/NIAID also induced immune responses with no safety issues in a phase 1 clinical trial (Jackson et al 2020). Another phase 1 trial with adults at the age of 56 and older showed anti-SARS-CoV-2 immune responses after 2 nd immunization in all vaccinees with mild to moderate adverse reactions to the vaccine (Anderson et al 2020). InterVac.…”
Section: Covid-19 Candidate Vaccinesmentioning
confidence: 98%